(untitled) (Movimento-revista de educação, 2017)
NNestas notas trataremos das atuais condições do laço social e suas repercussões nocampo educacional, sobretudo no impacto destas últimas nas relações transferenciais,estabelecidas pelos alunos em direção aos professores. As relações entre o conceitode inconsciente político e transferência estão aqui contempladas na discussão dasrelações entre as relações entre alunos e professores. Abordaremos as reflexões depsicanalistas e sociólogos no debate em torno das determinações inconscientespresentes no cotidiano das relações escolares entre professores e alunos eprocuraremos concluir com uma análise que privilegie o ato de professor em seu fazercotidiano. Palavras- chave: transferência; psicanálise; educação. In the text that follows the theme will deal with the current conditions of the social bondand its repercussions in the educational field, especially the impact of these ontransference relationships established by students towards teachers. The theoreticalrelations between the concept of political unconscious and transfer are contemplatedherein and are our main objective on the subject of discussion of the relationshipbetween students and teachers. Discuss the reflections of renowned authors on thesubject, especially psychoanalysts and sociologists to broaden the debate around the unconscious determinations present in the daily school relations between teachers andstudents and seek to conclude with an analysis of our reflections that favors the teacheract in his daily tasks. Keywords: transfer; psychoanalysis ; education.